From joint thinking to joint action: a call to action on improving water, sanitation and hygiene for maternal and newborn health - Campbell, Oona M R; Afsana, Kaosar; Hounton, Sennen; Benova, Lenka; Wijesekera, Sanjay; Mason, Elizabeth; Magoma, Moke; Graham, Wendy; Esteves Mills, Joanna; Cumming, Oliver; Curtis, Val; Velleman, Yael; et al. (© 2014 Public Library of Science, 2017)
This article was published in the PLoS Medicine [© 2014Public Library of Science] and The Journal's website is at: http://journals.plos.org/plosmedicine/article?id=10.1371/journal.pmed.1001771